Least unmatched price auctions: a first approach - Eichberger, Jürgen; Vinogradov, Dmitri V. (Discussion paper series, 2008)
Least-Unmatched Price Auctions have become a popular format of TV and radio shows. Increasingly, they are also applied in internet trading. In these auctions the lowest single (unique) bid wins. We analyze the game-theoretic solution of least unmatched price auctions when prize, bidding cost and the number of participants are known. We use a large data-set of such auctions in order to contrast actual behavior of players with game-theoretic predictions. In the aggregate, bidding behaviour seems to conform with a Nash equilibrium in mixed strategies.